2007
DOI: 10.1002/mds.21874
|View full text |Cite
|
Sign up to set email alerts
|

Validity of spiral analysis in early Parkinson's disease

Abstract: Spiral analysis is an objective, easy to administer noninvasive test that has been proposed to measure motor dysfunction in Parkinson disease (PD). We compared overall Unified Parkinson Disease Rating Scale Part III scores to selected indices derived from spiral analysis in seventy-four patients with early PD (mean duration of disease 2.4 +/- 1.7 years, mean age 61.5 +/- 9.7 years). Of the spiral indices, degree of severity, first order zero crossing, second order smoothness, and mean speed were best correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 25 publications
5
97
2
2
Order By: Relevance
“…Brain pathology reports were available for one subject (family A) and 2 previously deceased family members (from family C). C:301 had extensive testing after the diagnosis of A-T, including neuro-ophthalmologic examination and quantitative motor physiology testing (tremor analysis 18 and spiral analysis 19 ). No individuals harbored either a DYT1 or DYT6 mutation.…”
Section: Methods Standard Protocol Approvals Registrations and Patimentioning
confidence: 99%
“…Brain pathology reports were available for one subject (family A) and 2 previously deceased family members (from family C). C:301 had extensive testing after the diagnosis of A-T, including neuro-ophthalmologic examination and quantitative motor physiology testing (tremor analysis 18 and spiral analysis 19 ). No individuals harbored either a DYT1 or DYT6 mutation.…”
Section: Methods Standard Protocol Approvals Registrations and Patimentioning
confidence: 99%
“…These studies demonstrate that the pathology causes a worsening in the graphic movement execution and therefore PD patients are impaired in the execution of the automatic movements of writing and drawing (Caligiuri et al, 2006;Lange et al, 2006;Tucha et al, 2006). Spirography is a standard method to test the presence of PD symptoms, such as micrographia or tremor, or to study the strategies adopted by the patients in order to partially counter their deficit (Saunders-Pullman et al, 2008;Longstaff et al, 2006;Longstaff et al, 2003). In particular, hand-drawn spirals allow the study of micrographia and of the motor strategies adopted by the subjects [5,[7][8], because the subjects can freely choose the dimensions of the spiral and their drawing velocity.…”
Section: Assessment Of Motor Capabilitiesmentioning
confidence: 99%
“…In particular, hand-drawn spirals allow the study of micrographia and of the motor strategies adopted by the subjects [5,[7][8], because the subjects can freely choose the dimensions of the spiral and their drawing velocity. Several studies, in fact, observed that during a spiral hand-drawing task the spiral radius was shorter for the PD subjects than for the healthy subjects, leading to spirals of smaller dimensions (Saunders-Pullman et al, 2008).…”
Section: Assessment Of Motor Capabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…By using this property this device can detect the movement of a subject following standard drawing patterns placed on it [27; 49; 50; 51; 52; 53; 54; 55; 56] Subjectively interpreted in previous decades, nowadays the digital spirography can provide quantitative data of the movement control [57]. The spirography has been considered valid and reliable to diagnose early Parkinson's disease [58], essential tremor [59] and to distinguish tremulous parkinsonian patients with normal presynaptic dopaminergic imaging from tremulous patients with Parkinson's disease [60]. In general, the signals are recorded and stored for posterior analysis.…”
Section: Washington Heights-inwood Genetic Study Of Essential Tremor mentioning
confidence: 99%